TINJAUAN KEPASTIAN HUKUM PERPAJAKAN ATAS UPAYAHUKUM SENGKETA TERKAIT PENGAMPUNAN PAJAK (TAX AMNESTY) (Lex Jurnalica, 2019)
AbstractThe tax amnesty program initiated by the Government in 2016, provides forgiveness in the form of tax write-offs, not subject to administrative and criminal sanctions for taxpayers who report assets that have not been paid tax. In the process of filing a tax amnesty, a new dispute is very likely to arise. This paper discusses how the legal remedies for a Tax Amnesty dispute can be carried out by the Taxpayer? And how are the implications of the issuance of Minister of Finance Regulation No. 165 / PMK.03 / 2017 in terms of the principle of legal certainty? This research uses a juridical-normative method with data collection tools in the form of document studies consisting of primary and secondary legal materials, including interviews with related sources. In the Tax Amnesty Act, all disputes related to Tax Amnesty are resolved through a lawsuit attempt to the Tax Court, while additional provisions in the Minister of Finance Regulation, on SKPKB disputes issued in the case of implementing tax amnesty, are settled through legal remedies as in the General Provisions Act and Taxation Procedures, namely objections, then appeals, or requests for cancellation / reduction of the Tax Assessment Letter, in addition to direct litigation efforts. Therefore, the authors suggest a revised regulation in the form of a revision of Law Number 11 Year 2016 regarding Tax Amnesty, especially in the section on legal remedies. Keywords: Taxpayers, tax amnesty, disputes related to Tax Amnesty AbstrakProgram pengampunan pajak yang diinisiasi oleh Pemerintah pada tahun 2016, memberikan pengampunan berupa penghapusan pajak yang terutang, tidak dikenakan sanksi administrasi dan pidana bagi Wajib Pajak yang melaporkan harta yang belum dibayar pajaknya. Dalam proses pengajuan pengampunan pajak sangat mungkin timbul sengketa baru.Tulisan ini membahas tentang bagaimanakah upaya hukum atas sengketa Tax Amnesty dapat dilakukan oleh Wajib Pajak? Serta bagaimana implikasi terbitnya Peraturan Menteri Keuangan Nomor 165/PMK.03/2017 ditinjau dari asas kepastian hukum?Penelitian ini menggunakan metode yuridis-normatif dengan alat pengumpulan data berupa studi dokumen terdiri dari bahan hukum primer dan sekunder, diantaranya dilakukan wawancara dengan narasumber terkait. Dalam Undang-Undang Pengampunan Pajak, segala sengketa terkait Tax Amnesty diselesaikan melalui upaya gugatan ke Pengadilan Pajak, sedangkan ketentuan tambahan dalam Peraturan Menteri Keuangan, atas sengketa SKPKB yang terbit dalam hal pelaksanaan pengampunan pajak, diselesaikan melalui upaya hukum sebagaimana dalam Undang-Undang Ketentuan Umum dan Tata Cara Perpajakan, yakni keberatan, kemudian banding, atau permohonan pembatalan/pengurangan atas Surat Ketetapan Pajak, disamping upaya gugatan langsung. Maka dari itu, penulis menyarankan adanya penyempunaan pengaturan berupa revisi Undang-undang Nomor 11 Tahun 2016 tentang Pengampunan Pajak (Tax Amnesty) khususnya pada bagian pengaturan upaya hukum. Kata kunci: Wajib pajak, pengampunan pajak, sengketa terkait tax amnesty